Peran Kebijakan Pendidikan Berbasis Teknologi dan Motivasi Siswa di Era Digital - Tengku Darmansah; Elsa Elitia Hasibuan; Aina Ul Mardiyah Ray; Mulia Ardiansah Harahap; Suhada Aulia Fahra Harahap (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The digital era has brought significant changes in the world of education, especially in the implementation of technology-based policies to support the learning process. Technology-based education policies aim to improve the quality of learning through the integration of digital tools such as learning software, e-learning platforms and internet-based applications. In addition, student motivation is an important factor in the successful implementation of this technology. This research discusses the role of technology-based education policies in increasing learning effectiveness and how student motivation influences learning outcomes in the digital era. This study uses qualitative methods with a case study approach in educational institutions at various levels. The research results show that policies that support adequate technological infrastructure, training for teaching staff, and technology-based curriculum development can increase student engagement and achievement. On the other hand, students’ intrinsic and extrinsic motivation is greatly influenced by digital environments that are interactive and support personal learning. Therefore, integration between technology-based education policies and efforts to increase student motivation is the key to educational success in the digital era.